Keputusan pemerintah berbasis laporan keuangan dalam perspektif politik anggaran - Sudano, I Putu; Subawa, Nyoman Sri (Universitas Merdeka Malang, 2020)
This study aims to determine the extent uses of data and information that contain in the regional financial report (LPKD) is used in decision making by the Provincial Government of Bali in preparing the APBD. The research method used is a qualitative descriptive analysis by comparing the concept of decision making for budgeting according to Undang-Undang Nomor 23 Tahun 2014 concerning Regional Government with its application in the Provincial Government of Bali and the concept of decision making theory. Based on the results of the study it was found that the decision making in the preparation of the Bali Province APBD there were several weaknesses, including the lack of a link between the decision making in the preparation of the APBD of the local government financial reports. Also, the preparation of the Bali Provincial Government's APBD which is still based on Permendagri nomor 13 tahun 2016 concerning the evaluation of regional regulation designs, has not accommodated the performance and utilization of data, as well as information presented in the financial statements. Thus, the use of information data in the regional government financial reports is not optimal as a decision for the preparation and design of the APBD.Â DOI:Â 10.26905/pjiap.v5i1.3863